Regulating national firms in a common market - Sara Biancini (Center for Economic Studies and ifo Institute (CESifo), 2008)
We consider the regulation of national firms in a common market. Regulators can influence the production of national firms but they incur in a positive cost of public funds. First, we show that market integration is welfare improving if and only if the efficiency gains compensate for the negative public finance effect (related to business stealing). We also show that supranational competition can have very different consequences on the rent seeking behaviour of firms, depending on cost correlation and ex-ante technological risk. Finally, we characterize the global optimum and show how it can be sustained in a decentralized bargaining solution.
Keywords: L43; L51; F15; 330; regulation; competition; market integration; cost of public funds; Marktintegration; Regulierung; Wettbewerb; Makroökonomischer Einfluss; Gesamtwirtschaftliches Anlagevermögen; Agency Theory; Theorie